The Effect of Tripotassium Ethylene Diamine Tetraacetic Acid (K3EDTA) Blood Sample Shelf Time at Room Temperature on Hemoglobin Levels - Supri Hartini; I Gede Andika Sukarya; Widia Putri Pratiwi; Endah Wahyutri (UPT Publikasi Ilmiah Universitas Islam Bandung, 2025)
Hematological examination is essential for clinical diagnostics. The accuracy of hemoglobin measurements depends on the proper handling of pre-analytical samples. Storage of tripotassium ethylene diamine tetraacetic acid (K3EDTA) blood samples for too long at room temperature can lead to erythrocyte changes that affect test results. This study aims to determine the effect of K3EDTA blood sample storage time at 1 hour, 6 hours, and 24 hours at room temperature on hemoglobin levels. This comparative analysis study was carried out at the Hematology Laboratory, Diploma III Medical Laboratory Technology Program, Health Polytechnic Ministry of Health of East Kalimantan, on November 4–5, 2024. The study used 42 venous blood samples collected in K3EDTA tubes from 25 men and 17 women aged 18–55 years. Hemoglobin levels were measured using the cyanmethemoglobin method at three time points: 1, 6, and 24 hours at room temperature (20–25°C). Statistical analysis used one-way analysis of variance (ANOVA), followed by the post hoc Tukey's honestly significant difference (HSD) test. The mean hemoglobin values at 1, 6, and 24 hours were 14.8, 15.2, and 14.9 g/dl (male) and 13.3, 14.3, and 13.3 g/dl (female), respectively. ANOVA showed significant differences (p=0.001). Post hoc analysis revealed substantial differences between 1-hour and 6-hour storage (p=0.001) and between 6-hour and 24-hour storage (p=0.003), but not between 1-hour and 24-hour storage (p=0.766). In conclusion, storage time has a significant effect on hemoglobin measurements, with critical changes occurring at 6 hours, providing evidence-based guidance for pre-analytical quality assurance.